A novel dual-task paradigm with story recall shows significant differences in the gait kinematics in older adults with cognitive impairment: A cross-sectional study - Ali, Nawab; Liu, Jin; Tian, Huifang; Pan, Wei; Tang, Yao; Zhong, Qian; Gao, Yaxin; Xiao, Ming; Wu, Han; Sun, Cuiyun; Wu, Ting; Yang, Xi; et al. (Frontiers in Aging Neuroscience, 2022)
Objective: Cognitive and motor dysfunctions in older people become more evident while dual-tasking. Several dual-task paradigms have been used to identify older individuals at the risk of developing Alzheimer’s disease and dementia. This study evaluated gait performance under dual-task conditions in older adults with mild cognitive impairment, subjective cognitive disorder, and normal cognition. Design and setting: This is a cross-sectional, clinical based study carried out at the Zhongshan Rehabilitation Branch of First Affiliated Hospital of Nanjing Medical University, China. Participants: We recruited 82 community-dwelling participants and sorted them into MCI (n = 24), SCD (n = 33), and normal cognition (n = 25) groups based on neuropsychological tests. Their mean age was 71.9 (5.20) years, and male-female ratio was 42/40. Intervention: Each participant performed one single-task walk and four dual-task (DT) walks: DT 1, subtracting serial sevens; DT 2, naming animals; DT 3, story recall; and DT 4, words recall. Outcome and measures: Kinematic gait parameters of speed, knee peak extension angle, and dual-task cost were obtained using the Vicon Nexus motion capture system and Visual 3D software. A mixed effect linear regression model was used for analysis. Results: The difference in gait speed under DT story recall was 0.099 m/s, (P = 0.04) between MCI and SCD. Knee peak extension angle under dual-task story recall and words recall was higher in the MCI group compared to the NC group (P = 0.001). DT cost was higher in the dual-task story recall test than all other Dual-task conditions.